ANALYSIS OF STUDENT'S MISCONCEPTIONS IN SOLVING MATHEMATIC LOGIC PROBLEMS - Nurul Astuty Yensy; Agus Susanta; Dina Apryani; Hidayatulloh Hidayatulloh (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
AbstrakKarakter matematika bersifat hirarkis yaitu adanya keterkaitan antar satu konsep dengan konsep lainnya, sehingga akan sangat fatal jika mengalami miskonsepsi seperti keliru membuat sebuah generalisasi pada materi Logika Matematika dalam mata kuliah Matematika Dasar, sehingga jika terjadi miskonsepsi terus-menerus dapat menimbulkan kegagalan pemahaman konsep pada mata kuliah selanjutnya seperti Kalkulus dan Matematika Diskrit. Penelitian ini bertujuan mengidentifikasi miskonsepsi pada peserta mata kuliah Matematika Dasar di Program Studi Pendidikan Matematika Universitas Bengkulu pada tahun akademik 2021/2022 saat pembelajaran materi Logika Matematika. Metode yang digunakan yaitu pemberian tes diagnostik berbentuk essay, dan tingkat keyakinan dalam menjawab dengan menggunakan Certainty Response Index. Instrumen tes berupa tes diagnostik. Teknik pengumpulan data menggunakan lembar tes. Analisis data dilakukan terhadap uraian jawaban serta tingkat keyakinan dalam memberikan jawaban. Hasil penelitian menunjukkan bahwa pembelajaran Logika Matematika memberikan dampak miskonsepsi pada peserta mata kuliah Matematika Dasar berkisar 4 - 43% dengan identifikasi miskonsepsi tertinggi terjadi pada pokok bahasan tentang penyimpulan suatu pernyataan dan uji validitas argumen menggunakan hukum premis. Tingkat  miskonsepsi terendah terjadi pada uji argumen menggunakan tabel kebenaran. Rata-rata persentase tingkat miskonsepsi mahasiswa sebesar 21%. AbstractIt will be disastrous if there is a failure to comprehend the concepts or experience a misperception because mathematics has a hierarchical nature, so there is a relationship between one notion and another. One of the common errors making students in Mathematical Logic courses for Basic Mathematics is concluding or making erroneous generalizations. The University of Bengkulu's study program in mathematics education requires the completion of this course. Continuous misconceptions may make it difficult to understand the concept in later studies, including calculus and discrete mathematics.During the 2021–2022 academic year, participants in the Basic Mathematics course at Bengkulu University's Mathematics Education Study Program had misconceptions about the information they were learning about mathematical logic. A diagnostic test in the form of an essay is administered, and the Certainty Response Index is used to gauge the respondent's level of confidence. Test equipment in the form of a diagnostic test was the tool employed in this study. To collect data, test sheets that were distributed to students during the final semester exams were used. On the description of the answers and the degree of confidence in providing answers, data analysis was done. The findings indicated that learning mathematical logic had an impact on participants in the Basic Mathematics course in terms of misconceptions ranging from 4 to 43%, with the highest identification of misconceptions occurring on the topics of concluding a statement and determining the veracity of arguments using premise law. The argument test employing the truth table has the lowest level of misinterpretation. There were 21% average misconceptions among students.